Exploring the Implications of English as an International Language in Reading Instruction - Moh. Rif'attullah; Putra, Fahry Rizaldy (Universitas Nusantara PGRI Kediri, 2024)
The global expansion of the English language has sparked a growing demand for English education, transforming it into a tool for both local communication and international pursuits. This shift has led to a departure from mere imitation of native speakers towards embracing English as an International Language (EIL). English has evolved from being a language of a few dominant nations to a global lingua franca, resulting in profound implications for English language instruction. The English as an International Language (EIL) program emphasizes the multifaceted role of English in a globalized world. This paper discuss about English as an International Language (EIL) on the pedagogy of reading instruction within the Indonesian educational milieu, where English functions as a foreign language. It delves into the importance of reading as a fundamental skill for academic and professional success, highlighting the complexity of reading as an active cognitive process. Three theoretical perspectives on reading are discussed: the traditional bottom-up approach, the cognitive top-down processing approach, and the meta-cognitive perspective. Each perspective offers valuable insights into effective reading instruction. The paper provides the implication of English as the International Languagefor teaching reading, encompassing pre-reading activities that build vocabulary and background knowledge, during-reading strategies to promote active engagement with the text, and post-reading activities that encourage critical thinking and discussion. It emphasizes the need for a balanced approach that combines psycholinguistic and linguistic components in EFL reading instruction.